Linear habitats across a range of farming intensities contribute differently to dipteran abundance and diversity. Issue 3 (12th October 2020) - Ahmed, Karzan S. D.; Volpato, Alessio; Day, Michael F.; Mulkeen, Collette J.; O'Hanlon, Aidan; Carey, John; Williams, Christopher; Ruas, Sara; Moran, James; Rotchés‐Ribalta, Roser; ÓhUallacháin, Daire; Stout, Jane C.; et al.
Abstract: While the value of linear farm habitats for the protection and enhancement of farmland biodiversity in general is known, less is understood about their contribution to Diptera, especially those with different ecological requirements. In this study, we examined the impact of a range of linear farm habitats in agricultural grassland on Syrphidae and Sciomyzidae (Diptera) both of which provide important ecosystem services. Species richness and abundance for each family were measured across five different linear habitat types (dense and open hedgerows with/without adjacent watercourses and watercourses only). While dense hedgerows with adjacent watercourses showed the greatest numbers of Syrphidae species and individuals, open hedgerows with adjacent watercourses had significantly more Sciomyzidae species and individuals than dense hedgerows without watercourses or open hedgerows only. Syrphidae species richness was significantly correlated with the flowering plant species richness of linear habitats, while Sciomyzidae species richness was correlated with a habitat quality score for grasslands adjacent to the linear habitats. Overall, Syrphidae and Sciomyzidae species richness and community composition are shown to reflect a farming intensity gradient with significantly greater species richness for both families on extensive farms. Our results suggest that different dipteran taxa which utilise linear habitats may have different requirements. This has implications for future agri‐environmental schemes in the context of how we assess the conservation value of linear habitats on farmlands. Abstract : We studied the response of two different dipteran taxa (Syrphidae and Sciomyzidae) to linear farm habitats across a gradient of farming intensities in Ireland using bi‐directional malaise traps. Syrphidae and Sciomyzidae show different responses to linear farm habitat types with significantly more species and individuals of Sciomyzidae recorded in open hedgerows adjacent to watercourses and watercourses only. Low‐intensity farming practices and habitat quality appear to play a key role for sustaining dipteran diversity in agricultural lands with significantly greater species richness on extensive farms.